2020
DOI: 10.1155/2020/2136297
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Cutting and Fracturing of Rock Plate with One Side Fixed and Three Sides Free

Abstract: Conical pick is a rock cutting tool that is commonly used in roadway driving. Pick wear frequently happens in the course of breaking hard rock. The current paper shows a new method to solve the problem of pick wear. The rock is preslit with the saw blade and then broken by the conical pick. In order to study the cutting force and features of rock fragment, the numerical model is built between rock plate and conical pick. And element erosion is added in the code to obtain the fracture result. The rock plate cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to the investigation of Lu et al 21 , 23 and the investigation of the paper, the cutting process of rock plate under three side constraints, two adjacent side constraints, and one side constraint are studied. The cutting force is different with different cutting conditions for the same kind of rock plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the investigation of Lu et al 21 , 23 and the investigation of the paper, the cutting process of rock plate under three side constraints, two adjacent side constraints, and one side constraint are studied. The cutting force is different with different cutting conditions for the same kind of rock plate.…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al 19 studied the cutting performance of conical pick in the rock cutting process. Lu et al 20 24 proposed a combined cutting method of saw blade-pick and studied the cutting force of rock under different conditions. Wang et al 25 , 26 researched the effects of the cutting parameters of diamond sawblades on cutting rock and investigated the relationship between cutting force and cutting parameters of the conical pick in the rock cutting process.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [18], by establishing rotary cutting model of point attack pick, demonstrated that lower rotary angle and higher cutting angle were beneficial for reducing pick wear. Lu et al [19][20][21] proposed a multi-free-surface-rockcutting method under different constraints and carried out a numerical simulation study on cutting force in crushing process. Jeong et al [22] used the smooth particle hydrodynamics (SPH) technique to build the rock and conical pick interaction mode and the Drucker-Prager model to simulate the brittle fracture.…”
Section: Introductionmentioning
confidence: 99%